The Prevalence of Malaria among Children in Ethiopia: A Systematic Review and Meta-Analysis - Yalewayker Tegegne; Abebaw Worede; Adane Derso; Sintayehu Ambachew (Journal of Parasitology Research)
Background. Malaria is one of the most public health important and life-threatening parasitic infections caused by the protozoan parasite. Since children are immunologically naive to the malaria parasite, they are the main vulnerable groups. During malaria infection, they might have a complication of anemia, cerebral malaria, coma, respiratory distress, and a decrease in cognitive and behavioral improvement. Therefore, this review was aimed at determining the pooled prevalence of malaria among children in Ethiopia. Methods. The current systematic review and meta-analysis were conducted based on the guideline of Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement guideline. Electronic bibliographic databases such as Google Scholar, PubMed, and Science Direct were used for searching relevant literature. Besides, the Joanna Briggs Institute Meta-Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI) was used for critical appraisal of studies. Using the STATA 14 software, the pooled Meta logistic regression was computed to present the pooled prevalence with a 95% confidence interval (CI). Result. The overall estimated pooled prevalence of malaria among children in Ethiopia was 9.07 (95% CI: 6.32, 11.82). Subgroup analysis based on malaria signs and symptoms showed that the pooled prevalence of malaria among asymptomatic and symptomatic children was 6.67% (95% CI: 0.36, 12.98) and 27.17% (95% CI: 18.59, 35.76), respectively. Conclusion. The findings revealed a high prevalence of malaria among children in Ethiopia. As a result, still there is a need of improving and rechecking the existing malaria prevention and control measures of the country.